2015
DOI: 10.1038/ki.2015.238
|View full text |Cite
|
Sign up to set email alerts
|

α-Klotho is unstable in human urine

Abstract: α-Klotho is an interesting new biomarker in kidney and cardiovascular disease. As α-Klotho is primarily expressed in renal epithelial tissue, various papers have reported α-Klotho concentrations in urine. As these studies did not address the reliability of urinary α-Klotho measurements and as urine is known to be a complex milieu, we investigated the stability of α-Klotho in both fresh catheter and fresh voided urine. α-Klotho was measured in these fresh urine samples and in the same samples under several othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Measuring α-Kl in urine was not feasible because testing urine samples for measures of α-Kl levels revealed that urinary α-Kl is not stable [ 104 – 106 ]. Furthermore, urine samples stored at − 80 °C and – 20 °C degrade when exposed to room temperature or after repeated freeze-thaw cycles [ 107 ], emphasizing that urine samples are not an alternative source for assessing α-Kl levels.…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…Measuring α-Kl in urine was not feasible because testing urine samples for measures of α-Kl levels revealed that urinary α-Kl is not stable [ 104 – 106 ]. Furthermore, urine samples stored at − 80 °C and – 20 °C degrade when exposed to room temperature or after repeated freeze-thaw cycles [ 107 ], emphasizing that urine samples are not an alternative source for assessing α-Kl levels.…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…A positive correlation between αKlotho levels (serum and urine) and eGFR has been further characterized in adult CKD patients (Akimoto et al, 2012; Hu et al, 2011; Kim et al, 2013; Kitagawa et al, 2013; Ozeki et al, 2014), although only 24-h urine αKlotho but not serum αKlotho has been shown to be independently associated with eGFR change (Akimoto et al, 2012). However, questions about the stability of αKlotho in the urine have emerged (Adema, Vervloet, Blankenstein, & Heijboer, 2015). Therefore, a standardized urine protocol is required.…”
Section: αKlotho Deficiency As a Biomarker Of Ckdmentioning
confidence: 99%
“…Timing of Klotho delivery is also critical as soluble Klotho has been shown to be highly unstable in the blood and urine (169) and prevention of degradation may be essential. Numerous compounds have been approved for use in CKD but with only some positive outcomes seen suggesting the extent of reactivating and or replacing Klotho and its effects are yet to be clarified (170).…”
Section: Exercisementioning
confidence: 99%